Vesículas extracelulares: ações no microambiente tumoral e possíveis aplicações terapêuticas - Pachane, Bianca Cruz (Universidade Federal de São Carlos, 2024)
Extracellular vesicles (EVs) are particles delimited by a bilipid layer, secreted by cells for intercellular communication. EV release is favored under certain conditions, such as in cancer, where it interferes in multiple processes including the metastatic cascade and the tumor microenvironment. Studying the basic and applied biology of EVs enables the elucidation of new mechanisms of interest to human health, suggesting new therapeutic potentials. In this work, we explored the adhesive characteristic of EVs for in vitro applications, investigating their adsorption on glass surfaces using super-resolution microscopy and proposing a novel method for utilizing common laboratory materials for advanced applications. We investigated the detailed characteristics of EVs from breast cancer cells through proteomics, observing a clear difference in protein composition between hypoxic and normoxic vesicles. In cellular studies, the self-signaling of hypoxic EVs favored cell invasion under optimal oxygen conditions. In co-culture models using cells from the tumor microenvironment, we verified that hypoxic EVs act to recapitulate the cellular phenotype, maintaining cell cohesion in tumor and promoting a pro-tumoral microenvironment. Scaling up the study for potential therapeutic applications, we investigated the internalization of model EVs by human B cells ex vivo, corroborating previous findings in primate models and enabling further advancements in pharmacokinetic and biodistribution studies.
Extracellular vesicles: function in the tumor microenvironment and possible therapeutic outcomes
Keywords: Vesículas extracelulares; Câncer de mama; Biologia molecular; Extracellular vesicles; Breast cancer; Molecular biology; CIENCIAS BIOLOGICAS::BIOQUIMICA; CIENCIAS BIOLOGICAS::GENETICA